2005
DOI: 10.1007/s00247-005-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Reversible acute methotrexate leukoencephalopathy: atypical brain MR imaging features

Abstract: In addition to mostly asymptomatic classical MTX neurotoxicity, MTX may induce severe but reversible unusual leukoencephalopathy. It is important to recognize this clinicoradiological presentation in the differential diagnosis of acute neurological deterioration in children treated with MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…15 This type of encephalopathy is characterized by the presence of a T2 high-intensity area in the cortex and subcortical white matter, seizures lasting several days, and normalization of the MRI within 3 months. With regard to differential diagnosis, patient 1' s MRI abnormalities were also suspected to be the result of direct invasion of leukemic cells, despite the lack of leukemic cells in the cerebrospinal fluid, due to the presence of gadolinium-enhanced nodules.…”
Section: Discussionmentioning
confidence: 99%
“…15 This type of encephalopathy is characterized by the presence of a T2 high-intensity area in the cortex and subcortical white matter, seizures lasting several days, and normalization of the MRI within 3 months. With regard to differential diagnosis, patient 1' s MRI abnormalities were also suspected to be the result of direct invasion of leukemic cells, despite the lack of leukemic cells in the cerebrospinal fluid, due to the presence of gadolinium-enhanced nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Ziereisen et al [72] showed that at the end of therapy in 90 patients treated with MTX for ALL or non-B malignant non-Hodgkin lymphoma, 15 (17%) had T2 hyperintensities of whom 6 were symptomatic for acute LE, and 9 were asymptomatic. Interestingly, the spatial distribution of the hyperintensities differed in the two groups: asymptomatic subjects had localized, deep periventricular WM changes, and symptomatic subjects had hyperintensities in the supratentorial cortex, cerebellar cortex, cortical and subcortical WM, and thalamus.…”
Section: Magnetic Resonance Diffusion Imaging Studiesmentioning
confidence: 99%
“…This complication presents several months to years after therapy and may lead to severe neuropsychological impairment (Ziereisen et al, 2006).…”
Section: Chronic Leukoencephalopatymentioning
confidence: 99%